Gangguan Skizofrenia Ditinjau melalui Pendekatan Neuropsikologi - Muhammad Aldwin Priyatama; Natasya Azahra; Laila Indra Lestari (Flourishing Journal, 2023)
Schizophrenia is a severe mental disorder that affects an individual's thoughts, feelings, and behavior. Data indicates that the prevalence of schizophrenia in Indonesia is relatively high. This research aims to examine schizophrenia from a neuropsychological perspective, with a focus on the need for information regarding schizophrenia and its impact on the behavior of individuals with the condition. The research employs a literature review method. Based on the findings of the conducted research, it is evident that the causes of schizophrenia are primarily attributed to biological factors such as monozygotic twins, psychosocial factors, and environmental factors. Individuals with schizophrenia have abnormal brain. Abnormalities in brain structure among individuals with schizophrenia include white matter structure, decreased volume in the hippocampus, amygdala, thalamus, nucleus accumbens, and intracranial volume, hypoactivation in the left frontal lobe, as well as decreased electrical potential in the parietal lobe. When the brain, which typically functions cohesively, experiences abnormal structural conditions, it impacts the overall functioning of the brain and subsequently affects the behavior of individuals with schizophrenia. Abnormalities in brain structure lead to changes in cognitive function, memory, the limbic system, executive system, and abnormalities in the release of dopamine and serotonin. AbstrakSkizofrenia merupakan gangguan jiwa berat yang memengaruhi pikiran, perasaan, dan perilaku individu. Data menunjukkan bahwa penderita skizofrenia di Indonesia cukup tinggi. Penelitian ini dilakukan untuk mengkaji gangguan skizofrenia ditinjau melalui perspektif neuropsikologi dan urgensi pada penelitian ini terletak pada kebutuhan akan informasi mengenai skizofrenia dan pengaruhnya terhadap perilaku penderitanya. Penelitian ini menggunakan metode literature review. Berdasarkan hasil penelitian yang dilakukan, diperoleh hasil yang menunjukkan bahwa penyebab dari skizofrenia secara garis besar disebabkan oleh faktor biologis seperti kembar monozigot, psikososial, dan lingkungan. Penderita skizofrenia memiliki struktur otak abnormal. Abnormalitas struktur otak pada pengidap skizofrenia mencakup struktur white matter, penurunan volume pada hipokampus, amigdala, thalamus, nucleus accumbens, volume intrakranial, hipoaktivasi pada lobus frontal kiri, dan penurunan potensial listrik pada lobus parietal. Otak yang pada dasarnya bekerja secara bersamaan ketika strukturnya mengalami kondisi yang abnormal akan memengaruhi sistem kerjanya secara keseluruhan sehingga berpengaruh pada perilaku penderita skizofrenia. Abnormalitas pada struktur pada otak menyebabkan perubahan pada fungsi kognitif, memori, sistem limbik, sistem eksekutif, dan abnormalitas pada pelepasan dopamin dan serotonin.